KESETARAAN HAK DALAM PENDIDIKAN (STUDI PADA SEJARAH PERJUANGAN RAHMAH ELYUNUSIYAH DALAM MEMPERJUANGKAN HAK-HAK WANITA DALAM PENDIDIKAN) - Cikka, Hairuddin (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
For most Indonesians, a priori attitudes towards women in school are still the main domain of daily life. Just look at how the term kitchen-well-mattress is so popular among the people. This expression wants to emphasize that as powerful and as smart as any woman, in the end the